DANCE AND QUALITY OF LIFE PROMOTION IN DOWN SYNDROME: A VIEW ON DEPRESSIVE AD SELF-ESTEEM ASPECTS - Santana, Tainah Lima Sousa; Adorno, Evanilza Teixeira; Teixeira-Machado, Lavinia (International Journal of Research -GRANTHAALAYAH, 2018)
Down Syndrome (DS) adult often isolates himself from the world, due to social participation difficulty in understanding everything that surrounds him. In this context, dance assumes a substantial role in facilitating communication process, as it offers new ways of expressing ideas and feelings. The aim of this study was to investigate the effects of dance in quality of life, depressive and self-esteem aspects in DS. Method: This is a case report, longitudinal, descriptive, retrospective and prospective study, with dance class, twice a week, and public presentations, during four years. It was analyzed quality of life, depression index and self-esteem. Results: During the years, participant presented a gradual improvement in quality of life; the frequency and intensity of depression and anxiety symptoms decreased; she improved index of corporal satisfaction and in the self-esteem. Conclusion: Study reached the proposals in quality of life, depression, body satisfaction index and self-esteem.